2020
DOI: 10.1101/2020.08.04.20167932
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Viral cultures for COVID-19 infectivity assessment – a systematic review (Update 4)

Abstract: We report the results of a review of the evidence from studies comparing SARS-CoV-2 culture with reverse transcriptase polymerase chain reaction (rt-PCR), as viral culture represents the best indicator of current infection and infectiousness of the isolate. We identified fourteen studies succeeding in culturing or observing tissue invasion by SARS-CoV in sputum, naso or oropharyngeal, urine, stool and environmental samples from patients diagnosed with Covid-19. The data are suggestive of a relation between the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
116
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 57 publications
13
116
0
Order By: Relevance
“…Similarly, viral cultures of respiratory specimens have been found to be positive for 8–18 days with an average time of 10 days in patients with mild forms of COVID‐19 and for up to 32 days in patients with severe COVID‐19 267–270 . Clearly, SARS‐CoV‐2 has been cultured from many clinical samples 270 . Moreover, viable SARS‐CoV‐2 has been cultured from the air in a hospital room 271 .…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, viral cultures of respiratory specimens have been found to be positive for 8–18 days with an average time of 10 days in patients with mild forms of COVID‐19 and for up to 32 days in patients with severe COVID‐19 267–270 . Clearly, SARS‐CoV‐2 has been cultured from many clinical samples 270 . Moreover, viable SARS‐CoV‐2 has been cultured from the air in a hospital room 271 .…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%
“…It is important to realize that positive cultures of SARS‐CoV‐2 from the upper respiratory tract are found less frequently than RT‐PCR positive upper respiratory tract samples. Lower respiratory tract infections and stool cultures appear to have viable SARS‐CoV‐2 for approximately 1 month 267–270 . Antiviral therapy aimed at reducing the SARS‐CoV‐2 viral load would clearly benefit COVID‐19 patients as well as potentially reducing the spread to others.…”
Section: Therapy Of Sars‐cov‐2 Infections Based On the Pathogenesis Omentioning
confidence: 99%
“…One fundamental challenge is that proper evaluation of any point-of-care test destined for mass screening requires a robust and reliable way to identify true infectiousness: we need a reference standard against which the new test’s performance can be compared. Viral culture is one option, but culture based tests are hard to run and have high failure rates 5…”
Section: Testing Conundrumsmentioning
confidence: 99%
“…It correlates with symptoms,4 and people with low Ct values (indicating more viral material) are those most likely to be infectious 5. Using a low maximum Ct value (around 3056) has been suggested to reduce problematic detection of dead virus,6 but it will also miss early infection and rising infectiousness in both presymptomatic and symptomatic people. The measurement error of Ct values is non-trivial, and measurements vary between manufacturers and laboratories 7.…”
mentioning
confidence: 99%
“…Tom Jefferson, an epidemiologist for the Nordic Cochrane Centre and coauthor of a preprint paper examining viral cultures for assessing covid-19 infectivity,3 said that, while evidence showed that PCR tests were effective, the number of false positives they yielded must be taken into account when deploying them.…”
Section: False Positivesmentioning
confidence: 99%